The Role of Human Development Quality and Investment in Promoting Sustainable Economic Growth in Indonesia - Muhammad Bagus Ramadhan; Satria, Dias (Journal of Development Economic and Social Studies, 2025)
This study aims to examine the influence of the Human Development Index (HDI) and investment on sustainable economic growth in Indonesia from 2019 to 2023. The research employs a quantitative approach using panel data analysis from 34 provinces in Indonesia. It also includes two control variables—namely the Open Unemployment Rate and Regional Government Expenditure Budget—to assess their effects on the Environmental Quality Index as an indicator of sustainable economic growth. The findings reveal that the HDI, measured through Life Expectancy and Average Years of Schooling, has a positive and significant impact on sustainable economic growth. However, investment—represented by Foreign Direct Investment (FDI) and Domestic Investment (DI)—does not show a significant effect. Interestingly, the Open Unemployment Rate has a positive influence, which contradicts theoretical expectations, while the Regional Government Budget (APBD) has no meaningful impact. These results underscore the importance of improving human resource quality to support sustainable economic development, as well as the need to reassess investment direction and regional budget management.un